Subject-specific literacy in Physical Education and Health - the case of Sweden - Lundin, Katarina; Schenker, Katarina (Curriculum studies in health and physical education, 2022)
The overall aim of this paper is to introduce a new way of analysing and understanding the framing and potential of Physical Education and Health (PEH) practice. Focusing on subject-specific literacy, which is defined as an abstract and generalising language, containing words and concepts typical for a specific subject [Nestlog, B. E. (2019). Ämnesspråk - en fråga om innehåll, röster och strukturer i ämnestexter [subject-specific literacy - a question about content, voices and structures in subject specific texts]. HumaNetten Nr, 42, 9-30], we, in this paper, particularly stress and reiterate the need for a verbalised subject-specific literacy of PEH [Larsson, H., & Nyberg, G. (2017). 'It doesn't matter how they move really, as long as they move.' Physical education teachers on developing their students' movement capabilities. Physical Education and Sport Pedagogy, 22(2), 137-149; Wright, J. (2000). Bodies, meanings and movement: A comparison of the language of a physical education lesson and a feldenkrais movement class. Sport, Education and Society, 5(1), 35-49]. Since the subject-specific literacy of a subject constitutes a framework for the subject regarding content, pedagogy and assessment, we argue that linguistic analysis is crucial when it comes to better our understanding of PEH practice. Drawing on a linguistic analysis framework, the four most common textbooks used in Swedish PEH practice are analysed. The analysis of the PEH textbooks involves: defining the characteristics of the core concepts, identifying the semantic relations between the concepts, creating hierarchical systems of concepts and exploring what appears as the core content of the PEH subject. The results highlight how explicit ways of talking about all areas of the PEH curriculum are missing [Wright, 2000]. In particular, the results show that concepts primarily relating to 'sports' dominate in comparison to 'health', and that health content is permeated by a biomedical perspective, which is mirrored in the subject-specific literacy related to it. In addition, the concepts related to sports are specific, often physically palpable and denote dynamic activities, such as interval training, reps [repetitions], sets, HRmax, and static strength, whereas concepts related to health are instead abstract and static.